Use of an antigen trapping elisa kit for field diagnosis of trypanosoma evansi infections in dromedary camels (camelus dromedarius). - Waithanji, Elizabeth M. (University of Nairobi, 1993)
The studies described in this thesis were conducted to evaluate field application of the antigen-detection tube Enzyme Linked Immunosorbent Assay (ELISA) kit developed by Nantulya (1989) for diagnosis of Trypanosoma evansi infections in camels. The study was carried out on a herd of 100 camels in a T. evansi endemic area of Marsabit District, Northern Kenya. Blood samples were collected from each camel on four occasions; twice in the dry season and twice in the wet season. A total of 394 samples were collected. The results obtained using the tube-ELISA kit were compared with those of antigen trapping microplate ELISA, packed cell volume (PCY), the buffy coat technique (BCT) , and antibody ELISA. From each camel 3 ml of blood was collected by jugular venipuncture into a vacutainer tube containing ethylene diamine tetra acetate (EDTA) as anticoagulant, mixed and stored in a cool place. The EDT A blood was used for the following tests in the field: Packed cell volume (PCY) determination, buffy coat smear and antigen trapping tube ELISA. Simultaneously, lOml blood was collected from each camel into a silicon coated vacutainer tube for serum separation. The serum was separated 12 hours after collection, transported to the laboratory and stored at -200C until required for tube and microplate antigen trapping ELISA, and antibody ELISA. For tube ELISA, 500,LLI of whole blood or serum were used per tube and each sample was tested in duplicate. Fifty microlitres of serum were used per well in the antigen trapping microplate-ELISA, while 10 - 20,LLI were used in antibody ELISA. An optical density greater than twice that of the negative control serum was regarded as positive in the case of microplate ELISA. The criterion for positivity in tube ELISA was development of a visible green colour in the tube. Anaemia was the only presenting clinical sign: PCV values below 25 % were recorded in 7% of the blood samples examined. However, anaemia did not correlate well with other findings and was thought to have been due to factors other than trypanosomiasis. Trypanosomes were observed in the buffy coat in 1% of the samples examined, while antigens were detected in 10% of the samples by tube ELISA both in the field and in the laboratory, and in 5% by microplate ELISA. Antibodies were detected in 45 % of the samples by antibody ELISA. The differences in the ability to detect infection of antigen trapping tube-ELISA, the microplate ELISA, the BCT and antibody ELISA were all statistically significant. These findings indicated that of all the tests carried out, antibody ELISA obtained the highest prevalence rates of infection. However, the presence of antibodies in the blood does not necessarily indicate that the animal has an active infection. Thus, the high prevalence rates of infection detected by antibody ELISA could be due to persistence of antibodies in cured animals. Of all the tests that detect active infections, the antigen trapping tube- ELISA, whether performed in the field using whole blood or in the laboratory using serum, obtained higher prevalence rates of infection than the microplate antigen trapping ELISA and the BeT. The tube ELISA was easy to perform in the field and the results were obtained within three hours after sampling all the animals. Thus, it would be possible, using this test, to treat the positive animals before they are released from the "boma". Regarding sensitivity and specificity of the three field applicable tests, namely; tube-ELISA using both whole blood and serum, and the BCT, tube-ELISA using whole blood was the most sensitive and ranked second after the BeT in specificity. The BeT was, however, the least sensitive. These findings support the use of tube-ELISA and BCT as complementary tests in the field diagnosis of camel trypanosomiasis.